The impact of Kersen leaves (Muntingia calabura L.) extract on Mus musculus with hypercholesterolemia - Sion Benu; Anita Amat; Arley Telussa; Rr Listyawati Nurina (Acta Biochimica Indonesiana, 2024)
Background: Hyperlipidemia, a condition marked by elevated levels of total cholesterol and related lipids, poses significant health risks. The potential cholesterol-lowering effects of Kersen leaves (Muntingia calabura L.), which are rich in flavonoids, saponins, and tannins, warrant investigation. Despite the recognized benefits of Muntingia calabura L., its potential, particularly from the Nusa Tenggara Timur (NTT) region, still needs to be explored. Objective: This study aimed to assess the effect of Kersen leaves extract, sourced from arid regions of NTT, on hypercholesterolemia in Mus musculus. Methods: Healthy male white mice (Mus musculus) were used in the experiment and divided into five groups: a normal group, a negative control group, and three treatment groups receiving a high-cholesterol diet supplemented with Kersen leaves extract at doses of 75, 150, and 300 mg/kg body weight, respectively. Total cholesterol levels were measured using the Easy Touch GCU monitoring system. Statistical analysis was conducted using the Paired T Test to compare the pre and post data in each group. Results: A high-cholesterol diet for 14 days significantly increased body weight and total cholesterol levels in male white mice (Mus musculus). Meanwhile, treatment with Kersen leaves extract at 300 mg/kg body weight effectively mitigated the elevation in cholesterol levels. Conclusion: Kersen leaves extract (Muntingia calabura L.) significantly reduced hypercholesterolemia in Mus musculus, suggesting its potential as a natural therapeutic agent for cholesterol management. Further research is necessary to elucidate the underlying mechanisms of action and evaluate its clinical applicability.